The constable has blundered: the exclusionary rule, crime, and corruption - Signorelli, Walter P. (Carolina Acad. Press, 2010)
Unequal justice -- Justice denied : betrayal of the victims -- Searching for balance -- Far more crime -- Suppressing voluntary confessions -- State rebellions -- New York's false foundation -- Disarming the police -- Freed criminals and new victims -- Flight and confusion -- Exclusionary rule corruption -- Arguments for and against -- Irreconcilable conclusions -- Equal protection of the laws -- More effective remedies -- The Roberts court -- Conclusions